Want to ask us a question? Click here

Browse Questions

Ad |

0 votes

0 votes

- \(E(x)\)=\(\sum\)p\(_i\)X\(_i\)
- \(E(y)^2\)=\(\sum\)p\(_i\)X\(_i\)\(^2\)

\(E(x)\)=\(\sum\)p\(_i\)X\(_i\)=\(\Large0\times\;\frac{1}{5}\;+1\times\;\frac{2}{5}\;+2\times\;\frac{1}{5}\;+3\times\;\frac{1}{5}\)

=\(\Large\frac{3}{10}\;+\;\frac{8}{5}\;+\;\frac{9}{10}\;=\;\frac{28}{10}\;=\;\frac{14}{5}\)

\(E(y)^2\)=\(2\;E(x)\) proved

Ask Question

Take Test

x

JEE MAIN, CBSE, NEET Mobile and Tablet App

The ultimate mobile app to help you crack your examinations

...